In vitro fracture resistance of premolar teeth restored with fibre‐reinforced composite posts using a single or a multi‐post technique. (6th May 2016) - Fráter, Márk; Forster, András; Jantyik, Ádám; Braunitzer, Gábor; Nagy, Katalin; Grandini, Simone
Abstract: The purpose of this study was to evaluate the reinforcing effect of fibre‐reinforced composites (FRC) applied in premolar teeth with different techniques and minimally invasive post space preparation. Fifty extracted and endodontically treated premolar teeth were used. The teeth were divided into five groups ( n  = 10) depending on the restorative technique (Groups 1–5). Group 1: one single conventional post, Group 2: one main conventional and one collateral post, Group 3: one elastic post, Group 4: one main elastic and one collateral post, and Group 5: individual post formed of elastic posts. After cementation and core build‐up, the specimens were submitted to static fracture resistance test. Fracture thresholds and fracture patterns were measured and evaluated. Group 4 showed the highest average fracture resistance among the tested groups. The multi‐post techniques (group 2 and 4) exhibited statistically higher fracture resistance compared to group 1. Regarding fracture patterns, there was no statistically significant difference between the tested groups. Within the limitations of this study, the application of multiple elastic or conventional FRC posts or a single elastic post in the same root canal is beneficial in terms of fracture resistance compared to a single conventional FRC post. The elasticity or the number of posts did not influence the fracture patterns.